PHOTOVOLTAIC DEVELOPMENT FROM NEW ORDER REGIME TO REFORMATION REGIME IN INDONESIA: PERSPECTIVE OF TECHNOLOGICAL INNOVATION SYSTEM - Anugerah Yuka Asmara; Toshio Mitsufuji (STI Policy and Management Journal, 2017)
PV has been firstly introduced in Indonesia by government as part of new and renewable enegies (NREs) since new order regime. During this regime, directive of PV development was totally determined by strong role of government. Afterwards, in reformation regime, role of enterprises to develop PV appeared when government issued regulation about use of local products as well as formation of the directorate of NREs at Ministry of Energy and Mineral Resource (ESDM) in 2010. To capture phenomena of PV development during new order regime to reformation regime, technological innovation system (TIS) is used on this study. This study is a qualitative analysis using case study method developed by Yin. Finding of this study is that PV projects and its technology cannot be massively developed without intervention of government both in new order regime and reformation regime.